The Critical Comparison of the Green Parties’ Phenomena between Indonesia and Thailand - Eko Priyo Purnomo, Achmad Nurmandi, dkk (DOAJ, 2012)
The green activists realize that government policies do not enough support sustainability. Therefore, they want to make major breakthrough in dealing that issues. Establishing a green party could be an appropriate solution for implementing the green ideas. Besides, this paper attempts to analise the green parties’ phenomena in Indonesia and Thailand. The research has chosen the study areas, which are Indonesia and Thailand because Indonesia and Thailand have many similarities such as demography, geography, and social. The essay, which describes to compare the green party phenomena in Indonesia and Thailand, will focus on the SWOT analysis of the green party and political and social context in each country. Besides, this essay will analyse two things. Firstly, it will look at the social and political contexts. In this context, it will try to describe the historical party in both Indonesia and Thailand. It also will examine the cultural and social contexts that manipulate the party phenomena. Even, the biggest Muslim country in the world, Indonesia has already implemented the democracy values. It is a good example that Islam is compatible with democracy. The green parties already exist but they could not perform very well. Whilst Thailand has also chosen monarchy constitutional and the king pay attention on green issue but the green parties have not been existed.